POSITIVE ORGANIZATION BEHAVIOR PENGARUHNYA TERHADAP KINERJA PT PLN (PERSERO) UPT PADANG - Mardiah, Nila; Chandra, Hari; Salym, Ayu Monnica (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2022)
This study aims to analyze positive organizational behavior consisting of emotional intelligence, positive communication and work happiness and its effect on the performance of employees of pt pln (persero) upt padang. Source of data by distributing questioners to pln employees related to the variables studied and then processed with spss using the t test to see the effect of variable x on y, and see the effect of x on simultaneously. . From the processed data results reveal that emotional intelligence has a positive effect on employee performance, then positive communication and work happiness have a positive effect on the performance of pt pln employees.